Studi Deskriptif Pemanfaatan Sampah Anorganik Dalam Membuat Karya Benda Konstruksi - Ayu Fitriana; Hasnawati (Universitas Bengkulu, 2023)
This study aims to describe the process and the results of using anorganic waste in making construction work in class IV B SDN 45 Bengkulu City. This type of research is qualitative research, with participant observation techniques, and qualitative descriptive methods. The subjects in this study were all students of class IV B SDN 45 Bengkulu City, totaling 26 students. The research instrument used was a human instrument (the researcher himself), using observation guidelines and interview guidelines. Data collection techniques in the form of observation, interviews, and documentation. Data analysis was carried out during the process of making the work and after the work was finished by referring to the fine arts elements and the principles of fine arts. The results of the study are (1) The process of making construction art objects begins with preparing the materials and tools used, namely colorful straws, white glue, pedestals / scissors, and scissors / cutter, followed by the implementation of making works from preparing several slabs of straws , making the size of each slatted straw, gluing plates together, and developing variations in shape. (2) The results of construction works made using the art elements guidelines as well as visual art principles, namely point, line, shape, shape, color, texture, dark light. Then, the principle of unity, balance, rhythm, emphasis, proportion, and harmony / harmony.